Prompt and non-prompt J/ψ elliptic flow in Pb+Pb collisions at √sNN = 5.02 TeV with the ATLAS detector - Alconada Verzini, María Josefina (2018)
The elliptic flow of prompt and non-prompt J/ψ was measured in the dimuon decay channel in Pb+Pb collisions at √ sNN = 5.02 TeV with an integrated luminosity of 0.42 nb−1 with the ATLAS detector at the LHC. The prompt and non-prompt signals are separated using a two-dimensional simultaneous fit of the invariant mass and pseudo-proper decay time of the dimuon system from the J/ψ decay. The measurement is performed in the kinematic range of dimuon transverse momentum and rapidity 9 < pT < 30 GeV, |y| < 2, and 0–60% collision centrality. The elliptic flow coefficient, v2, is evaluated relative to the event plane and the results are presented as a function of transverse momentum, rapidity and centrality. It is found that prompt and non-prompt J/ψ mesons have non-zero elliptic flow. Prompt J/ψ v2 decreases as a function of pT, while for non-prompt J/ψ it is, with limited statistical significance, consistent with a flat behaviour over the studied kinematic region. There is no observed dependence on rapidity or centrality.